Divine ambiguity: A philosophical inquiry into God"s uncertain decisions - Durodolu, Oluwole O. (HTS teologiese studies, 2024)
The debate surrounding the nature and attributes of God as presented in the Bible has garnered significant attention and critique from various philosophical perspectives like Friedrich Nietzsche, Bertrand Russell and David Hume. This philosophical critique emphasises the inconsistency in the nature of God and challenges traditional theological beliefs. The expression of regret by the God of the Bible in Genesis 6:6 raises philosophical dilemmas regarding divine attributes and the problem of evil. The contradiction between God’s regret and the affirmation of his creation as good underscores fundamental questions about divine omniscience, omnipotence and benevolence. The presence of evil and suffering in the world poses a significant challenge to the notion of a loving and all-powerful God. Examples of human suffering, such as slavery, colonisation, apartheid and natural disasters, further highlight the complexity of reconciling divine attributes with the existence of evil. Philosophically analysing biblical narratives, such as the story of Job, Noah’s flood and the plagues of Egypt, raises ethical concerns regarding divine justice and the moral agency of humanity. Additionally, the indiscriminate punishment of innocent individuals in these narratives challenges the credibility of a benevolent and compassionate God. The philosophical inquiry into the problem of evil and natural disasters underscores the need for a nuanced understanding of divine attributes and their implications for human existence.Contribution: The study encourages reflection on key questions about the nature of divinity, the morality of divine actions, and the compatibility of traditional theology with rational thought. It highlights how inconsistencies in certain biblical accounts challenge those trying to balance faith with reason and scientific understanding. While some may view these narratives as metaphors or allegories, others find it difficult to align them with their intellectual beliefs, resulting in tensions between religious faith and scientific rationality.